INVESTIGATION OF BIOCHEMICAL EFFECTS OF NANO ZINCOXCIDE (ZnO) IN SACCHAROMYCES CEREVISIAE - Ozsahin, D.; Demirkol, Y.; Okutan, T.; Kirecci, O. A. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2024)
Zinc-oxide nanoparticle (ZnO NP) is one of the metal oxide materials widely used in many fields due to its superior properties. Numerous studies have been conducted on the toxic effects of these NPs in biological systems; however, there is a limited number of studies investigating their effects on biochemical parameters. The aim of this study is to determine the effects of ZnO NP on some biochemical parameters and defense system in yeast (Saccharomyces cerevisiae) culture medium. The analysis (Gas chromatographic analysis) of fatty acids and sterols (ergosterol, campestrol, stigmasteol, betasitosterol) was performed. The results of the present study revealed that zinc oxide nanoparticles had various effects on biochemical parameters in S. cerevisiae yeast culture to which they were applied at different doses. A significant statistical difference was found between the control group and the other groups for biochemical parameter content. It is thought that the results of the antioxidant defense system will be a reference for similar studies on other living models and will contribute to the literature by supporting future studies using in vivo systems.
Keywords: nano-zinc oxide; fatty acid; GSH; vitamin; Saccharomyces cerevisiae